Left Atrial Diameter, Aortic Mean Gradient, and Hemoglobin for Risk Stratification in Patients Undergoing Transcatheter Aortic Valve Implantation. Issue 4 (28th February 2013) - Gotzmann, Michael; Thiessen, Anja; Lindstaedt, Michael; Mügge, Andreas; Ewers, Aydan
Abstract Background Transcatheter aortic valve implantation (TAVI) is an alternative treatment of severe symptomatic aortic stenosis (AS) in patients with high operative risk. In spite of favorable entire results, long‐term mortality of patients is high. Hypothesis The present study aims to identify independent preprocedural risk factors to improve risk stratification in these highly selected patients. Methods This prospective study included 202 consecutive patients with severe symptomatic AS and high operative risk (mean logistic European System for Cardiac Operative Risk Evaluation, 22 ± 17%; mean age, 79 ± 6 years; 107 female). Preprocedural comprehensive examinations were performed (laboratory, electrocardiography, echocardiography, cardiac catheterization). All patients received transfemoral or transaxillary TAVI with a CoreValve prosthesis (Medtronic, Minneapolis, MN). Results During a follow‐up of 535 ± 333 days, 56 patients (28%) reached the primary study end point (all‐cause mortality). Independent predictors of long‐term mortality were as follows: hemoglobin <12.5 g/dL (hazard risk [HR], 3.62; 95% confidence interval [CI], 2.025–6.468; P < 0.001), aortic mean gradient ≤41 mm Hg (HR, 2.16; 95% CI, 1.272–3.655; P = 0.004), and left atrial diameter > 42 mm (HR, 3.09; 95% CI, 1.588–6.019; P = 0.001). Our risk‐stratification model based on these independent predictors separated patients into 4 groups with high (74%), intermediate (37%), low (18%), and very low (3%) all‐cause mortality. Conclusions In patients undergoing TAVI, preprocedural assessment of hemoglobin, aortic mean gradient, and left atrial diameter provides independent prognostic information and therefore contributes to improved risk stratification in TAVI.